Diffusion of Environmental Awareness - Lösch, Stefanie; Okhrin, Ostap; Wiesmeth, Hans (Diffusion Fundamentals, 2017)
A high level of “environmental awareness” in the participating countries will likely raise the success of the Kyoto Protocol negotiated in Paris in 2015. In this context it is of interest to investigate the diffusion of environmental awareness, and also the (economic) factors, on which this diffusion depends. This paper addresses these questions for the regions of the Russian Federation, which are sufficiently diverse regarding cultural and economic issues. From a formal point of view, a “Multiple-Indicator-Multiple-Causes” (MIMIC) approach, based on a variety of “indicators” for environmental awareness, derived from search entries in c Yandex, and a variety of “causes”, economic and socio-economic factors, is applied. The empirical results point first to a strong dependence of environmental awareness on the level of GRP per capita. Moreover, the diffusion seems to spread from the eastern part of Russia towards the western regions.